Criminal law sanctions for misappropriation, embezzlement or seizure of property through abuse of office (Law and Safety, 2023)
The concept of criminal law sanctions has been analysed, the classification of criminal law sanctions for misappropriation, embezzlement or seizure of property through abuse of office has been studied, and the peculiarities of building criminal law sanctions for crimes under Article 191 of the Criminal Code of Ukraine have been revealed. It has been concluded that a sanction is a mandatory component of an article (or part of an article) of the Special Part of the Criminal Code of Ukraine which contains a model of the type and scope of punishment which is adequate to the social danger of a criminal act. The sanction reveals the legal aspect of criminal punishment, indicating its type and scope, while acting as a model of criminal punishment provided for the crime.One of the most important and necessary prerequisites for the court to determine the lawful and, therefore, appropriate punishment is strict compliance with the requirements of Article 65 of the Criminal Code of Ukraine on imposing punishment within the limits established in the sanction of the article of the Special Part providing for liability for the crime. Taking this requirement into account implies that in each particular case the court should be guided by the types and amounts of punishment provided for by the relevant sanction of the criminal law, as well as by the provisions of the General Part. This means that the sanction must be mandatory.The law should, of course, give judges a choice so that the sentence can be appropriate to the gravity of the offence and the person involved. However, this should not go beyond the limits of social justification and undermine the general deterrent function of criminal sanctions. Therefore, a judge must clearly know the rules by which he or she can assess the significance of a particular circumstance in order to determine the amount of punishment. This is the approach used in the draft CC of Ukraine.
Keywords: criminal law sanctions; punishment; criminal offences; imprisonment; release on probation.